Hyperbaric oxygen therapy in periodontal diseases - Swapna A. Mahale; Pankaj K. Kalasva; Sunil Vinayak Shinde (Wolters Kluwer Medknow Publications, 2013)
Hyperbaric oxygen (HBO 2 ) has been successfully used in several medical fields. The therapeutic effect is related to elevated partial oxygen pressure in the tissues. The pressure itself enhances oxygen solubility in the tissue fluids. HBO 2 has shown to affect angiogenesis, bone metabolism and bone turnover. Studies have been conducted to analyze the effects of HBO 2 therapy on periodontal disease. HBO 2 increases local oxygen distribution, especially at the base of the periodontal pocket, which inhibits the growth of anaerobic bacteria and allows the ischemic tissues to receive an adequate intake of oxygen sufficient for a rapid recovery of cell metabolism. It is increasingly being accepted as a beneficial adjunct to diverse clinical conditions. Nonhealing ulcers, chronic wounds and refractory osteomyelitis are a few conditions for which HBO therapy (HBOT) has been extensively tried out. The dental surgeons have found a good ally in HBOT in managing dental condition.